(untitled) (Global Journal of Management and Business Research, 2023)
Abstract- Employee innovative work behaviour is a key factor in an organization s survival and competitiveness in the global economy However only a few studies examined the impact of antecedents of employee innovative work behavior Hence aims to investigate the impact of idiosyncratic deals on employee innovative behavior and the perceived coworker distributive justice s role in this relationship The conceptual model was empirically tested by collecting data from 113 insurance agents in the Gampaha district in Sri Lanka The Partial Least Squares technique PLS a third-generation structural equation modeling technique SEM was used to analyze data in this study The study s findings revealed a significant impact of idiosyncratic deals on employee innovative work behavior Perceived coworker distributive justice significantly moderates the impact of idiosyncratic deals on employee innovative work behavior Hence this study broadened the theoretical understanding of i-deals innovative work behaviour and coworkers reactions to the organizations